PRO-CHILD POLICY: SAFEGUARDING THE NEXT GENERATION FROM THE THREAT OF VIOLENCE, NEGLECT AND EXPLOITATION - Salma Rozana; Rafika Nisa; Al-Amin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Pro-child policy is an important initiative in protecting and ensuring the welfare of the nation's next generation from the threat of violence, neglect and exploitation. A pro- child policy is a set of measures, regulations, programmes and initiatives designed and implemented by governments, institutions or organisations with the primary aim of protecting, promoting and fulfilling children's rights. It focuses on the best interests of children in various aspects of life, including health, education, security and well-being. The ultimate goal is to create a safe, supportive and conducive environment for children's optimal growth and development, and to protect them from various forms of abuse, neglect and exploitation. Pro-child policies include efforts to strengthen child protection systems, improve access to basic services, and ensure children's participation in decisions that affect their lives. With that, effective and sustainable pro- child policies not only protect children from immediate threats but also contribute to the long-term development of human capital, which is critical to the progress and sustainability of a nation.